Gas temperature measurement in internal cooling passages - Wang, Z; Ireland, P; Kohler, S (ASME, 1996)
The gas temperature distribution is important in the measurement and the definition of heat transfer to various gas turbine cooling problems. This paper describes a novel technique which employs encapsulated thermochromic liquid crystals on a fine nylon mesh to give virtually instantaneous gas temperature distribution measurement. The hue value of the liquid crystals on a fine nylon mesh to give virtually instantaneous gas temperature response crystal, in the range of 22-40°C, and for a narrow band crystal from 29-31°C. Data processing issues specific to the application of liquid crystals on porous target are discussed and the results of investigations provided. Finally, applications that demonstrate the viability of the method are given.